Digital marketing communication practices and effectiveness - Lessons from the Small and Medium Enterprises(SMEs) restaurant industry in Malaysia - S. Ganesan, Gunalan (2025)
The restaurant sector in Malaysia has experienced rapid growth, driven by changing lifestyles, social demographics, and the influence of social media. This project investigates digital marketing communication practices and their effectiveness within the SME restaurant industry in Malaysia. The study addresses the knowledge gap regarding the challenges and successes of digital marketing among SMEs, emphasising the urgent need for comprehensive insights. The research evaluates various digital marketing communication strategies such as social media marketing, email campaigns, and content marketing and evaluates their impact on customer engagement and business growth. The findings reveal that while some SMEs have embraced digital marketing communication, there is a noticeable lack of comprehensive insights into its effectiveness and the challenges entrepreneurs encounter. The study identifies that digital marketing communication practices significantly enhance customer engagement and business growth. However, SMEs face high operating costs, competition from larger chains, and regulatory hurdles. The research also highlights the importance of knowledge in digital marketing communication and support programs in sustaining and growing the SME restaurant sector. The findings provide valuable insights for restaurant owners, marketers, and policymakers to enhance their digital marketing efforts and support the sustainability of SMEs in the competitive restaurant industry.